Nonlinear Finite Element Analysis of Steel Shear Walls with Perforations - Ashour, Rana (2016)
A Master of Science thesis in Civil Engineering by Rana Ashour entitled, "Nonlinear Finite Element Analysis of Steel Shear Walls with Perforations," submitted in January 2016. Thesis advisor is Dr. Mohammad AlHamaydeh. Soft and hard copy available.